PERANAN WANITA PEDAGANG SAYURAN TERHADAP PENDAPATAN KELUARGA DI PASAR PINASUNGKULAN KAROMBASAN MANADO - Dewanti ., Rakomole; Jenny ., Baroleh; Joachim N. K. Dumais (Sam Ratulangi University, 2016)
This study aims to determine the contribution of women vegetable vendors in supporting the family income. This study was carried from July to October 2015 in Pinasungkulan Market Karombasan Manado. Retrieval of data in the form of primary data and secondary data. The primary data obtained through interviews of 10 women vegetable vendors and secondary data obtained from relevant agencies, namely the Department of Market. Data presented in tables and descriptive analysis and to determine the contribution of revenue derived from the percentage of women between revenue wives to the family income. The results showed that women vegetable vendors in the market Pinasungkulan Karombasan have completed elementary school; hovewer most of them do not go on to further education. Woman vegetable merchant who became the object of research is a married woman and still a single. Husband incomes so low that cannot provide for the family to encourage his wife to work together, otherwise it because he wanted to utilize the time available. Women vegetable vendors have to pursue this work between 10 years to 35 years. Working hours of women vegetable vendors are between 8 to 19 hours per day with an average of 13 hours working hours per day. The activities carried out, namely the purchase of vegetables, vegetable cleaning, until the sale of vegetables. Types of vegetables studied were mustard greens (caisin), Chinese cabbage, kale and spinach which is a type of green leafy vegetables commercially. The biggest volume of purchasing / procurement for highland vegetables is mustard greens (caisin) which is an average of 150 bunches per day, and for the type of lowland vegetables are kale that is an average of 160 bunches per day. The average of their husband income was IDR 1.4875 million per month and the average income of wife IDR 2.014 million per month. Wives revenue was greater than husbands’ revenue, where the average contribution of wives was 50.01%, which means the wives have played an important role in supporting the family incomes.